2022
DOI: 10.3389/fendo.2022.1010472
|View full text |Cite
|
Sign up to set email alerts
|

Agouti-related protein as the glucose signaling sensor in the central melanocortin circuits in regulating fish food intake

Abstract: Agouti-related protein (AgRP) is a neuropeptide synthesized by AgRP/NPY neurons and transcribed as 132 amino acids in humans and 142 amino acids (AgRP1) in Japanese seabass (Lateolabrax maculatus) fish. AgRP neurons are activated by hormonal signals of energy deficits and inhibited by signals of energy surpluses and have been demonstrated to have the ability to sense the dynamics of blood glucose concentrations as the “glucose sensor” in mammals. It is widely recognized that AgRP is an endogenous antagonist of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
1
1
0
Order By: Relevance
“…In the Hy region, the feeding-related neuropeptides pro-melanin-concentrating hormone ( pro-MCH ) and agouti-related protein ( AgRP ) were significantly enriched. This finding is consistent with the hypothalamus’s role in controlling feeding and satiety in fish ( 55 , 56 ). Furthermore, the highly expressed stress-related genes in the Hy, including ACTH precursor peptide pro-opiomelanocortin ( pomc ), synthetase of catecholamine tyrosine hydroxylase 2 ( th2 ), and transcription factor of pomc NK2 homeobox ( nkx2 ), suggest that the Hy plays a crucial role in regulating the stress response ( 57 , 58 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the Hy region, the feeding-related neuropeptides pro-melanin-concentrating hormone ( pro-MCH ) and agouti-related protein ( AgRP ) were significantly enriched. This finding is consistent with the hypothalamus’s role in controlling feeding and satiety in fish ( 55 , 56 ). Furthermore, the highly expressed stress-related genes in the Hy, including ACTH precursor peptide pro-opiomelanocortin ( pomc ), synthetase of catecholamine tyrosine hydroxylase 2 ( th2 ), and transcription factor of pomc NK2 homeobox ( nkx2 ), suggest that the Hy plays a crucial role in regulating the stress response ( 57 , 58 ).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, higher GC and lower INS contents were also shown in the PS and GPS groups, which might respond to variations of corresponding serum glucose contents [35,38]. In addition, many studies have reported higher levels of AGRP could increase the appetite in animals [17,35,39]. Considering the lower FCR in the GTS and GPS groups, it is suggested that gelatinized polysaccharide (GTS and GPS) could improve feed utilization and subsequently enhance growth by increasing AGRP contents in largemouth bass.…”
Section: Discussionmentioning
confidence: 94%
“…Рецептор Г -это связанный с G-белком рецептор, через него опосредуются многие процессы, связанные с действием Г, например стимуляция выработки релизинг-факторов и повышение аппетита [16]. Параллельно с изучением Г внимание исследователей направлено на агути-белок (АБ), являющийся нейропептидом, вырабатываемым клетками гипоталамуса [17]. АБ является одним из самых мощных и продолжительных стимуляторов аппетита [18,19].…”
Section: эффекты грелина в физиологических условияхunclassified